Challenging the Mainstream Portrayal of Islam in Indonesian Screen Culture: Religious Representation in Hati Suhita Film - Khalimatu Nisa; Muhammad Nikmal Anas Alhadi (DINIKA : Academic Journal of Islamic Studies, 2024)
This article examines the representation of Islam in Indonesian screen culture, focusing on the genre of film Islami. It discusses the dominant portrayal of muslims piety and modernity in these films and explores the smaller number of films that depict pesantren culture, a manifestation of traditional Islam. The article analyzes the Hati Suhita film as a significant shift in representing a solid traditional Islam rooted in history, culture, and the modern values to shape religiosity. It highlights the film's exploration of a love triangle within an arranged marriage in a non-cliché manner through strength and resilience, grounded on Javanese philosophy and sufism, while promoting a gender justice perspective. It also discusses the film's impact on the pesantren community, and its role in becoming a convergence point between pesantren and screen culture, two domains that have been considered distant from each other. This article also observes that the success of this film is the result of a long endeavor to negotiate pesantren with popular culture. Overall, the article contributes to the ongoing discourse on the representation of Islam in Indonesian screen culture, and the intersection of tradition, modernity, and religion.